2017
DOI: 10.3390/ijerph14050524
|View full text |Cite
|
Sign up to set email alerts
|

Income-Related Inequalities in Access to Dental Care Services in Japan

Abstract: Background: This study aimed to evaluate whether income-related inequalities in access to dental care services exist in Japan. Methods: The subjects included beneficiaries of the National Health Insurance (NHI) in Chiba City, Japan, who had been enrolled from 1 April 2014 to 31 March 2015. The presence or absence of dental visits and number of days spent on dental care services during the year were calculated using insurance claims submitted. Equivalent household income was calculated using individual income d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
35
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(39 citation statements)
references
References 26 publications
2
35
0
1
Order By: Relevance
“…The present findings regarding income inequalities in access to dental care are consistent with those of previous studies . A systematic review and meta‐analysis on access to dental care including 7 395 697 participants from 28 countries showed that dental utilization was higher among countries with a higher human developmental index (HDI) .…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…The present findings regarding income inequalities in access to dental care are consistent with those of previous studies . A systematic review and meta‐analysis on access to dental care including 7 395 697 participants from 28 countries showed that dental utilization was higher among countries with a higher human developmental index (HDI) .…”
Section: Discussionsupporting
confidence: 91%
“…Finally, the present findings suggest a possible intervention policy to reduce income inequalities in access to dental care as mentioned above. While previous studies have reported inequalities in access to dental care and suggested financial/insurance‐related solutions for their reduction, our study presented another viewpoint.…”
Section: Discussionmentioning
confidence: 74%
See 1 more Smart Citation
“…This may be explained by their knowledge of oral health and attitude towards dental care utilization, in that the highly educated have a better knowledge and awareness of dental health than the less educated . Factors such as inadequate knowledge of oral health and deficient health literacy may create barriers to utilizing dental care among low‐income groups and cause income‐related inequality . In addition, the highly educated tend to be richer and can better afford dental care than the less educated.…”
Section: Discussionmentioning
confidence: 99%
“…It has been found that limited access to dental care and economic barriers have strong effects on oral health and its equity . However, pro‐rich inequality in dental care utilization has been found in both developed and developing countries . The studies on trends in disparities in the dental care utilization found the improvement of affordability and dental health insurance coverage may be the drivers to reduce inequality .…”
Section: Introductionmentioning
confidence: 99%